Functional Inequalities for Generalized Complete Elliptic Integrals with Two Parameters - Xiangkai Dou; Li Yin; Xiu-Li Lin (Journal of Function Spaces)
In this paper, we establish some functional inequalities for generalized complete elliptic integrals with two parameters, such as estimation of bounds and mean inequalities. Our main results give (p,q)-analogues to the early results for classical complete elliptic integrals.